In-hospital prognostic role of coronary atherosclerotic burden in COVID-19 patients. Issue 11 (November 2021) - Fazzari, Fabio; Cozzi, Ottavia; Maurina, Matteo; Donghi, Valeria; Indolfi, Eleonora; Curzi, Mirko; Leone, Pier Pasquale; Cannata, Francesco; Stefanini, Giulio G.; Chiti, Arturo; Bragato, Renato Maria; Monti, Lorenzo; et al.
Abstract : Aims: Currently, there are few available data regarding a possible role for subclinical atherosclerosis as a risk factor for mortality in Coronavirus Disease 19 (COVID-19) patients. We used coronary artery calcium (CAC) score derived from chest computed tomography (CT) scan to assess the in-hospital prognostic role of CAC in patients affected by COVID-19 pneumonia. Methods: Electronic medical records of patients with confirmed diagnosis of COVID-19 were retrospectively reviewed. Patients with known coronary artery disease (CAD) were excluded. A CAC score was calculated for each patient and was used to categorize them into one of four groups: 0, 1–299, 300–999 and at least 1000. The primary endpoint was in-hospital mortality for any cause. Results: The final population consisted of 282 patients. Fifty-seven patients (20%) died over a follow-up time of 40 days. The presence of CAC was detected in 144 patients (51%). Higher CAC score values were observed in nonsurvivors [median: 87, interquartile range (IQR): 0.0–836] compared with survivors (median: 0, IQR: 0.0–136). The mortality rate in patients with a CAC score of at least 1000 was significantly higher than in patients without coronary calcifications (50 vs. 11%) and CAC score 1–299 (50 vs. 23%), P < 0.05. After adjusting for clinical variables, the presence of any CAC categories was not an independent predictor of mortality; however, a trend for increased risk of mortality was observed in patients with CAC of at least 1000. Conclusion: The correlation between CAC score and COVID-19 is fascinating and under-explored. However, in multivariable analysis, the CAC score did not show an additional value over more robust clinical variables in predicting in-hospital mortality. Only patients with the highest atherosclerotic burden (CAC ≥1000) could represent a high-risk population, similarly to patients with known CAD.